Discussing the role of circular RNA in the pathogenesis of non-alcoholic fatty liver disease and its complications - Yepmo, Melissa; Potier, Jean-Baptiste; Pinget, Michel; Grabarz, Anastasia; Bouzakri, Karim; Dumond Bourie, Aurore (Frontiers in Endocrinology, 2022)
Circular RNAs (circRNAs) are class of non-coding RNA, which are characterized by a covalently closed loop structure. Functionally they can act on cellular physiology, notably by sponging microRNAs (miR), regulating gene expression or interacting with binding protein. To date, circRNAs might represent an interesting, underexploited avenue for new target discovery for therapeutic applications, especially in the liver. The first characteristic of non-alcoholic fatty liver disease (NAFLD) is hepatic cholesterol accumulation, followed by its advanced form of the affection, nonalcoholic steatohepatitis (NASH), due to the occurrence of lobular inflammation, irreversible fibrosis, and in some cases hepatocellular carcinoma (HCC). Therefore, studies have investigated the importance of the dysregulation of circRNAs in the onset of metabolic disorders. In this review, we summarize the potential role of circRNAs in the development of metabolic diseases associated with the liver such as NAFLD or NASH, and their potential to become therapeutic strategies for these pathologies.